Sosialisasi dan Pelatihan Senam Bugar Pelajar Muhammadiyah bagi Guru dan Siswa Sekolah Muhammadiyah - Wening Nugraheni; Agung Widodo; Sayid Fariz bin Seh Abubakar (Jurnal Surya Masyarakat, 2024)
Muhammadiyah is the largest religious organization in Indonesia which has various charitable efforts, one of which is in the field of education. These charities range from kindergarten to tertiary levels spread throughout Indonesia, including in the city and district of Sukabumi, West Java. There are 13 Muhammadiyah schools in Sukabumi city and district ranging from elementary school to high school. Based on research, the level of physical fitness of students in the city and regency of Sukabumi is 21.77% in the poor category and 65.31% in the very poor category. Apart from that, based on the results of interviews and observations, it was found that physical education learning at school was not optimal and there were minimal alternative physical activities carried out at school. This socialization and training was carried out to provide knowledge and skills to physical education teachers and students regarding alternative physical activities that can be used to improve fitness for students. The method used in this socialization and training was to invite teacher and student representatives from each school partner to be provided with training. During the training, partners were very active in paying attention to the resource person's explanations and practising “Senam Bugar Pelajar Muhammadiyah”, starting from warm-up, core and cool-down movements. This activity provides benefits for partners, namely knowledge related to alternative physical activities for students and skills in providing “Senam Bugar Pelajar Muhammadiyah”.